Ease Of Doing Business: A Comparative Analysis in The Context of Global Economies (International Journal of Food and Nutritional Sciences, 2022)
Thanks to globalization, the entire world has become a village today. Every nation aspires to become a larger economic power, thus there is fierce competition to lower investment requirements in order to draw in global industry while also fostering an environment that encourages domestic entrepreneurship. Even though the Indian government enacted Liberalization, Privatization, and Globalization (LPG) in 1991, the country's business environment has not much improved, especially in practice, and it currently stands at 130th place out of 190 nations that took part in the 2017 Ease of Doing Business index. Many new entrants are discouraged from beginning a business due to the tiresome formalities needed. The Indian government has recently launched a number of programs to strengthen the country's economy, including Digital IndiaThe current study, "Ease of Doing Business: A Comparative Analysis in The Context of Global Economies," is exploratory in nature and is based on secondary data that was gathered from secondary sources that were accessible online, such as the Government of India portal, the World Bank Portal, and numerous e-research journals. The results indicate that the government's many initiatives have begun to bear fruit, as the process of conducting business in India has improved, moving up to 130 from 142 in 2015. India needs to put in more work and raise its worldwide position compared to the top ten nations in the index. Its ranking has also improved globally, rising from 142 in 2016 to 140 in 2017.